Accuracy of Occlusal Contacts of All-Ceramic Single Crowns Designed by Virtual Articulators from a CAD/CAM System: A Preliminary Evaluation - Yuan, Yun; Xu, Enxin; Xu, Xinrui; Huang, Hui (The International journal of prosthodontics, 2024)
To compare the static and dynamic occlusion of all-ceramic single crowns designed by mechanical and virtual articulators, by evalua6ng the accuracy of occlusal contacts of prostheses designed by virtual articulators and the feasibility of clinical application of CAD/CAM virtual articulators. Nine subjects with an average age of 27 years who needed crown repair were recruited. After preparation of the all-ceramic crowns, two zirconia crowns were designed and fabricated through digital procedures and traditional methods. The intraoral scanner, Geomagic software, and T-Scan analyzer were used to analyze the occlusal contact points, areas, and the occlusal force percentage peak before the treatment and after the two crowns were temporarily fixed. There was a significant difference in the number of occlusal contact points and areas between the mechanical group and control group (preoperation group), but there was no obvious difference between the virtual group and control group. The occlusal contact overlapping areas of the virtual-control group were significantly larger than those of the mechanical-control group. The occlusal force percentage peak of the tested teeth was slightly larger in the mechanical group than in the virtual group. The posterior single crown designed by a virtual articulator restored the intercuspal occlusal better than one designed by a mechanical articulator, and it produced less dynamic occlusal interference. This finding suggests that virtual articulators can provide guidance for the design and adjustment of the occlusal surface of posterior single crown prostheses.